Meningkatkan Prestasi Belajar Matematika Melalui Metode Pembelajaran Kooperatif Model Student Teams Achievement Division - Lindra Lindra (Pedagogi: Jurnal Ilmu Pendidikan, 2018)
In learning a clever child must help a less intelligent child, a strong child should help the weak, and each child should encourage each other to foster a strong learning motivation. This study is based on the problems: (a) How to improve student achievement by applying the cooperative learning method of STAD model? (b) How is the influence of STAD model of cooperative learning method toward student's learning motivation? The purpose of this research are: (a) Want to know the improvement of student learning achievement after application of cooperative learning method STAD model. (b) Want to know the influence of student learning motivation after applied STAD cooperative learning model method. This research uses action research for three rounds. Each round consists of four stages: design, activity and observation, reflection, and revision. The target of this research is a student of Class XI IPA 1 SMAN 2 Batang Anai. Data obtained informative test results, observation sheet of teaching and learning activity. From the analyst's result, it is found that the students' learning achievement has increased from cycle I to cycle III that is, cycle I (65,22%), cycle II (78,26%), cycle III (86,96%). The conclusion of this research is cooperative learning method STAD model can have a positive effect on student's motivation to study grade XI IPA 1 SMAN 2 BATANG ANAI, and this learning model can be used as one of mathematics learning alternative.